Cognitive Ability Profiles of Junior High School Students with High Mathematical Abilities in Numbers Material Based on TIMSS Domain - Puspasari, Magdalena Dwi; Mampouw, Helti Lygia (International Journal of Active Learning, 2019)
The study aimed to describe the cognitive ability of junior high school students in answering questions on whole and fraction numbers based on TIMSS domain. This is a descriptive qualitative research involving three junior high school students with high mathematical ability as the subjects, i.e.: KV, DA, and TE. The data colletion instruments were TIMSS questions on whole numbers and fraction and the interview guidelines. The data were analyzed by using TIMSS cognitive domain in the sections of knowing, applying and reasoning. The results indicated that the knowing stated in written by KV and in mind by DA. Meanwhile TE?s ability was limited to compute fractions and measure. While KV applied mathematical concepts in written, DA and TE applied them verbally. TE was less accurate in using the concept of whole numbers. In the context of reasoning, KV was able to propose various solutions, DA had a single solution to fraction qeustions, and TE was confined to fraction questions. The subjects made their conclusions only in written.